Cognitive Diversity in the Classroom: An Inquiry through Individual Difference in Cognition - Devkota, Mahadev (Madhyabindu Journal, 2022)
The purpose of this study is to explore the cognitive diversity in the classroom especially focusing on individual differences in cognition through different perspectives.Cognitive diversity plays an influential to form a diverse team to perform tasks requiring creativity. Every learners' has a unique and distinctive way of concept formation, problem-solving techniques, and shared meaning because of their diversity in terms of personality, ethnicity, economic status, gender, the ability of comprehension, personal values, attitudes, information-dispensation style, and most significantly how much learners' rely on various aspects of multiple intelligence such as visual-spatial, linguistic-verbal, logical-mathematical, bodily-kinesthetic, musical, interpersonal, intrapersonal, and naturalistic intelligence. Individuals vary in their cognitive performance because of their cognitive differences. This qualitative research employed descriptive methodology and documentary analysis along with using relevant secondary sources for the claim, supporting reasons, and finally to develop argumentation. The finding of this study shows that every learner has a unique and distinctive approach in terms of concept formation, problem-solving, information-dissemination, and shared meaning. Cognitive diversity plays a crucial role to enhance academic performance, work efficiency, and to conceptualize the diverse cognitive traits each student brings to the learning environment. However, some studies point out the drawbacks of cognitive diversity as it invites conflict, stress, misunderstanding, lack of collaboration, and gratitude among team members. It is recommended that educators should keep the learners' different intelligence profiles into consideration and design the activities accordingly.